The modern organizational environment: Communication, Networking and new technologies as driving forces for sustainability, progress & strategic alignment. - Markaki, Evangelia; Chadjipadelis, Theodore (International Conference on Business and Economics - Hellenic Open University, 2023)
The current study presents the driving sources and the challenges of the modern organizational environments. The New forms of communication, networking, the multicultural environment, and the structural issues in organizations as well as ethics are some of the challenges that the modern organizational environment deals with. We ask employees of different demographic background to evaluate all these new changes and challenges and we assess how people react towards these new characteristics. We also investigate how people believe organizations can integrate these new trends in compliance with an effective organizational performance. The use of the Conjoint Analysis and the scenario technique allow us to investigate and understand the significance of different characteristics or factors that influence the modern organizational environment and the coexistence of different generations in organizations. The Conjoint Analysis is a multidimensional analysis that can also provide information in a group but also in an individual level. This can help us to create interesting metrics for people and segmentations that lead to an organizational strategic design and sustainability. The present study can have applications in the business, social science, and politics environment. EL Classifications: G34, G14, M41. Key words: Strategic Alignment, Sustainability, Communication, Networking, Conjoint Analysis.